The belt and road initiative and the law of the sea - Zou, Keyuan (Maritime cooperation in East Asia, 2020)
"This volume provides a useful reference to policy and law makers, students and researchers, and the public for the Belt and Road Initiative in relation to ocean governance and marine activities in accordance with the United Nations Convention on the Law of the Sea"--